Serum Retinol Binding Protein 4 as a Potential Biomarker for Sarcopenia in Older Adults. Issue 1 (20th July 2022) - Chang, Chen-Lu; Li, Yan-Ru; Wang, Zhi-Yue; Li, Mei-Lin; Jia, Kai-Yue; Sun, Hui-Xian; Wang, Quan; Zhao, Can; Lu, Xiang; Gao, Wei
Abstract: Sarcopenia is characterized by progressive loss of muscle mass and function due to aging. Retinol-binding protein 4 (RBP4) is an adipokine with pro-inflammatory effects. However, the change of RBP4 concentration and its role in sarcopenia remains unclear. The aim of this study was to evaluate the association of serum RBP4 level with sarcopenia in the older adults. A total of 816 community-dwelling older adults aged ≥60 years were enrolled. Serum RBP4 was measured by enzyme-linked immunosorbent assay. Appendicular skeletal muscle mass index (ASMI), grip strength, and gait speed were measured. We found that serum RBP4 levels were higher in patients with sarcopenia when compared with those without sarcopenias (44.3 [33.9–57.7] vs 38.0 [28.0–48.4] μg/mL). Receiver operating characteristic curve analysis indicated that the optimal cutoff value of serum RBP4 level that predicted sarcopenia was 38.79 μg/mL with a sensitivity of 67.8% and a specificity of 53.3%. Multivariate logistic regression analysis showed that the subjects with a higher level of RBP4 had a higher risk of sarcopenia (adjusted odds ratio [OR] = 2.036, 95% CI = 1.449–2.861). Serum RBP4 concentration was negatively correlated with grip strength ( r = −.098), gait speed ( r = −.186), and AMSI ( r = −.096). Moreover, serum RBP4 levels were higher in patients with severe sarcopenia when compared with those with moderate sarcopenia (49.0 [37.3–61.2] vs 40.4 [31.3–51.2] μg/mL). Taken together, our results demonstrate that serum RBP4 level is correlated with the risk and severity of sarcopenia in the older adults, indicating that RBP4 might serve as a surrogate biomarker for the screening and evaluation of sarcopenia.